(untitled) (Ozone Therapy Global Journal, 2020)
Regardless of the cause, politraumatism in canines may result in wounds that require immediate treatment. Here we describe the clinical case of a dog with a 4.5c long polytraumatic injury of in the left hind leg, with a necrotic process that initial amputation above the tarsus was required. Localized ozone therapy was administered on the wound. The initial step was to submerge the injured leg (3c above the injury) in distilled water at a concentration of 17.5 µg (with a constant bubbling of 70 µg) for 15 minutes, followed by a bagging effort for 5 minutes at the same concentration. Excluding the bagging, the same procedure was followed for seven treatment sessions while gradually decreasing the concentration until reaching a concentration of 1.5 µg and constant bubbling of 5 µg). Every treatment session was completed with a dressing of the wound with ozonized oil of 800 IP. The wound resolved in 30 days, and there was only need to amputate 3 phalanges and not above the tarsus as initially forecast, requiring only eight treatment sessions . These findings suggest that the treatment is safe and effective. The recovery of the dog was fast, inexpensive and did not require pharmacologic treatment